The sustainability of forest management: assessing the impact of CIFOR criteria and indicators research - Spilsbury, M.J. (Center for International Forestry Research, 2005)
The Center for International Forestry Research (CIFOR) Criteria and Indicators (C&I) research responded to an international demand for science to help clarify the assessment of sustainable forest management through development and improvement of C&I. C&I help define standards for sustainable forest management and are now being used by many different groups. The impact study shows, through examination of public assessment reports, that certification, in turn, has led to large improvements in sustainable forest management on the ground. Substantial areas of forests have been certified, and the issues most closely associated with CIFOR research contributions to certification standards commonly feature in public records of certification audits.